YouTube Videos in Literacy Course: Students’ Response and Practice - Luh Ketut Sri Widhiasih (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2023)
Technology cannot be avoided in this 21st century era. The practice of using technology variated in education. This study has purpose to identify students’ response and practice of using YouTube in teaching literacy while introducing digital citizenship value. The design of this research was mixed method. The method of data collection were questionnaire, observation, and interview. While, the data collection instruments were list of close ended questionnaire, observation checklist, and list of interview question. The data gathered were analysed, presented, discussed, and concluded on this paper by using Interactive Model. The results showed that the use of YouTube in literacy classes in this case listening classes while inserting digital citizenship values got positive responses from the students. Moreover, the use of YouTube assessed by Triple E framework showed that the technology used focused on engaging students in more interactive listening activities while introducing new concept about digital citizenship.